An effective software architecture of islamic inheritance system employing structured paradigm - Rashed, Mustafa rashed; Rahman, Mohammad Osiur; Tabassum, Sadia; Nazib, Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2022)
Distribution of wealth of a deceased person among the heirs is a critical and complicated problem in Islamic jurisprudence system. In a Muslim society, the demand of a wealth calculation system is very high and plays a pivotal role in day-to-day life of Muslim families. In this paper, we propose a structured and well-defined software solution that employs structured software engineering approach using Data Flow Diagram (DFD), structure chart and program description language (PDL). The proposed system distributes shares among the heirs based on Islamic rules. Many such systems have been built by different govt agencies of different Muslim majority countries. Many of those systems are error prone and are not well defined from the software engineering perspective. In many cases, the software architecture of such systems is undisclosed and their applicability in many complex deceased-heir relationship provides wrong calculation. The proposed solution on the other hand, makes the successful use of software engineering approach to interpret Islamic Inheritance rules in a more manageable, scalable and maintainable fashion. The system is rigorously tested on different complex scenarios and the results are verified by Muslim family lawyers. The system is developed using C programming language and we make the source code open (https://github.com/sajidcsecu/IIS).